To strengthen or to shatter? On the effects of stratification on professions as systems. (14th September 2020) - Alvehus, Johan; Eklund, Sanna; Kastberg, Gustaf
Abstract: The aim of this article is to contribute to the literature on how stratification affects professions. Our case study is the 'first teacher reform' in Sweden, which introduced a more prominent position for some teachers. In this article, we elaborate six different first teacher types and analyse how these affect the profession. While elites are generally described as hybrids, we conclude that several of our types rather led to a de‐hybridization of roles, where managers became more administratively focused, and elites more anchored to professional tasks. We conclude that elite roles reveal various potentials in being strengthening/weakening or shattering/integrating to the profession, but, in contrast to other studies on professional elites, the majority of roles studied here are both strengthening and integrating to the profession. The study is qualitative and is based on 111 interviews, 12 weeks of shadowing and 53 observed meetings.